TL

Bài 3 : Tính nhanh

A) 11/15 + 5/7 + 2/7 + 4/15

B) 17/10 + 1/2 - 7/10

HT
13 tháng 9 2017 lúc 21:13

a) \(\frac{11}{15}+\frac{5}{7}+\frac{2}{7}+\frac{4}{15}\)

\(=\left(\frac{11}{15}+\frac{4}{15}\right)+\left(\frac{5}{7}+\frac{2}{7}\right)\)

\(=\frac{15}{15}+\frac{7}{7}\)

\(=1+1\)

\(=2\)

b) \(\frac{17}{10}+\frac{1}{2}-\frac{7}{10}\)

\(=\left(\frac{17}{10}-\frac{7}{10}\right)+\frac{1}{2}\)

\(=1+\frac{1}{2}\)

\(=\frac{2}{2}+\frac{1}{2}\)

\(=\frac{3}{2}\)

Bình luận (0)
H24
13 tháng 9 2017 lúc 21:11

A)11/15+5/7+2/7+4?15

  =( 11/15+4/15)+(5/7+2/7)

 =1+1

=2

B17/10+1/2-7/10

=17/10-7/10+1/2

=1+1/2

=3/2

k mik nha!

Bình luận (0)
LN
13 tháng 9 2017 lúc 21:12

A)\(\frac{11}{15}+\frac{5}{7}+\frac{2}{7}+\frac{4}{15}\)

\(=\left(\frac{11}{15}+\frac{4}{15}\right)+\left(\frac{5}{7}+\frac{2}{7}\right)\)

\(=1+1\)

\(=2\)

b) \(\frac{17}{10}+\frac{1}{2}-\frac{7}{10}\)

\(=\frac{17}{10}-\frac{7}{10}+\frac{1}{2}\)

\(=1+\frac{1}{2}\)

\(=\frac{3}{2}\)

okey nha

nếu mk làm đúng thì hãy ủng hộ mk nha

Bình luận (0)
VT
13 tháng 9 2017 lúc 21:13

a)11/15 + 5/7 + 2/7 + 4/15= (5/7 + 2/7)+(11/15 + 4/15)=1 + 1=2

b)17/10 + 1/2 - 7/10 =  17/10 - 7/10 + 1/2 = 1 + 1/2 = 3/2

Bình luận (0)
PC
13 tháng 9 2017 lúc 21:13

A)11/15+5/7+2/7+4/15=(11/5+4/15)+(5/7+2/7)=1+1=2

B)17/10+1/2-7/10=(17/10-7/10)+1/2=1+1/2=3/2

Bình luận (0)
NN
13 tháng 9 2017 lúc 21:15

a) \(\frac{11}{15}\)\(\frac{5}{7}\)\(\frac{2}{7}\)\(\frac{4}{15}\)

=  \(\frac{77}{105}\)+  \(\frac{75}{105}\) +  \(\frac{30}{105}\) + \(\frac{28}{105}\)

=  \(\frac{210}{105}\) =  \(2\)

Bình luận (0)
TD
13 tháng 9 2017 lúc 21:16

11/15 + 5/7 +2/7 +4/15 =11/15 + 4/15 + 5/7 + 2/7 =1 +1 =2                                                                                                                                                                                                                                                                                                                         17/10 +1/2 - 7/10 =17/10 - 7/10 +1/2 = 1 - 1/2  =1/2

Bình luận (0)
NN
13 tháng 9 2017 lúc 21:18

b) \(\frac{17}{10}\) + \(\frac{1}{2}\) - \(\frac{7}{10}\)

=  \(\frac{17}{10}\) + \(\frac{5}{10}\)+  \(\frac{-7}{10}\)

=  \(\frac{15}{10}\) =  \(\frac{3}{2}\)

Bình luận (0)

Các câu hỏi tương tự
HH
Xem chi tiết
NT
Xem chi tiết
BD
Xem chi tiết
NH
Xem chi tiết
LA
Xem chi tiết
BV
Xem chi tiết
NT
Xem chi tiết
DL
Xem chi tiết